2018
DOI: 10.1186/s12913-018-3598-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cost-sharing design characteristics on use of health care recommended by the treating physician; a discrete choice experiment

Abstract: BackgroundCost-sharing programs are often too complex to be easily understood by the average insured individual. Consequently, it is often difficult to determine the amount of expenses in advance. This may preclude well-informed decisions of insured individuals to adhere to medical treatment advised by the treating physician. Preliminary research has showed that the uncertainty in these cost-sharing payments are affected by four design characteristics, i.e. 1) type of payments (copayments, coinsurances or dedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Targeted therapy for HER2 + patients does not tend to be prescribed in Vietnam when it is known that patients cannot afford the treatment (personal communication). The effect of cost on doctor's prescribing behaviour and patient treatment decisions were documented elsewhere [28][29][30] and need further research in Vietnam. Polices involving higher HI coverage rate for targeted therapy and/or an OOP maximum (a cap on the amount of money that a patient pays for covered healthcare services plan/year) is likely to impact positively on access by patients to appropriate BC treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Targeted therapy for HER2 + patients does not tend to be prescribed in Vietnam when it is known that patients cannot afford the treatment (personal communication). The effect of cost on doctor's prescribing behaviour and patient treatment decisions were documented elsewhere [28][29][30] and need further research in Vietnam. Polices involving higher HI coverage rate for targeted therapy and/or an OOP maximum (a cap on the amount of money that a patient pays for covered healthcare services plan/year) is likely to impact positively on access by patients to appropriate BC treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Targeted therapy for HER2+ patients does not tend to be prescribed in Vietnam when it is known that patients cannot afford the treatment (personal communication). The effect of cost on doctor’s prescribing behaviour and patient treatment decisions were documented elsewhere [ 37 39 ] and need further research in Vietnam. Polices involving higher SHI reimbursement rate for targeted therapy and/or an OOP maximum (a cap on the amount of money that a patient pays for covered health services plan per year) is likely to impact positively on access by patients to appropriate BC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, at-fee copayments paid at point of care offer individuals clear and immediate information on the required payments in advance. In a hypothetical decision context, Salampessy and colleagues have demonstrated that such payments stimulate adherence to recommended healthcare [20].…”
Section: Discussionmentioning
confidence: 99%
“…We used data collected by Salampessy and colleagues and described in detail elsewhere [20]. In short, an online questionnaire was distributed by email among panel members of the Dutch Patient Federation in March and April 2016.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation